HUBUNGAN FAKTOR RESIKO KARIES DALAM SALIVA DENGAN INDEKS DMF-T PADA PENDERITA DM TIPE II DI RSCM SUB BAGIAN ENDOKRIN (Laporan Penelitian) - Buddiwati Punta; Edi Hartini Sundoro (Faculty of Dentistry, Universitas Indonesia, 2015)
Dental caries is a multifactorial disease. The most important factors in the development of caries is saliva. Reduced salivary secretion in patients with type 2 diabetes melitus to the occurrence of caries have yielded controversial results. The aim of the study was to find out whether the risk factors of the saliva i.e. saliva secretion rate, buffer capacity, salivary S. mutans, salivary Lactobacilli, alone or in combination, could be used for prediction of caries activity. Thirty patients with type 2 diabetes mellitus and age range 46-73 participated. Diabetic status was determined by fasting plasma glucose is >126mg/dl, 2-hour plasma glucose is >140mg/dl. Decayed, missing, and filled teeth indices were determined by means of clinical examination. Stimulated saliva with parafin was measured for flow rate and buffer capacity, level of S. mutans & Lactobacilli were analyzed with dentobuff and dentocult. There was no decrease in salivary secretion in patients with type 2 diabetes melitus. Significant corellation were found between buffer capacity, and combination of the S. mutans & Lactobacilli counts in caries activity.